(untitled) (European Journal of Child Development, Education and Psychopathology, 2019)
Perceived social support is crucial in the adolescent school behaviour, especially in school engagement. In general, a person’s close contexts promote his school engagement, but not all the sources of social support have the same effect. The objectives of this investigation are two: on the one hand (a) analyse the relation between perceived social support and school involvement; and on the other hand (b) identify the variability of perceived social support and school engagement based on sex and parents’ educational level. 323 students of Secondary Education of a high school of Vitoria-Gasteiz aged between 12 to 18 years old (M=14.41; DT=1.18) participated in the study, being 128 of them boys (40%) and 195 girls (60%). The questionnaires APIK (social support) and SEM (school engagement) were used. The obtained results prove that perceived social support correlates with school engagement, being the support from the teachers the one with the highest punctuations. According to the variability based on sex and parents’ educational level of the second objective, there are only differences in perceived social support, being them in favour of women.